Determination of total phenolic, flavonoid content and free radical scavenging activities of common herbs and spices. - Shirazi, Ovais Ullah; Khattak, Muhammad Muzaffar Ali Khan; Mohd Shukri, Nor Azwani; A., Mohd Nur Nasyriq (2014)
Antioxidants present in herbs and spices could be an effective tool to prevent the non-communicable diseases like cancer, diabetes and myocardial infarction as they have the capacity to stabilize the free radicals which are one of the causative factors of these diseases. This study aims to quantify the total phenolic and flavonoid content of commonly used herbs & spices and determination of their free radical scavenging activities expressed as inhibitory concentration (IC50). The results of this study depict that the tested herbs & spices have considerable amount ofphenols and flavonoids and a high scavenging power of free radicals.